Evaluation of individually ventilated caging system for laboratory animals - One year's experience - KOSTOMITSOPOULOS (Ν.Γ. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. G.; PARONIS (Ε. ΠΑΡΩΝΗΣ), E.; ALEXAKOS (Π. ΑΛΕΞΑΚΟΣ), P.; APERGIS (Ι. ΑΠΕΡΓΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
During the last decades, the use of individually ventilated caging system has become more and more attractive for housing laboratory rodents. Since the Animal Facility of the Centre for Experimental Surgery of the Foundation of Biomedical Research of the Academy of Athens was totally equipped with individually ventilated caging units, it was decided, after one year and a half of working experience, to perform an evaluation of the system, based on specific criteria. Individually ventilated caging system can contribute to the increased number of laboratory rodents housed within the animal facility by making better use of the available space, which is not always dedicated to animals. The system is flexible for the simultaneous support of research protocols with different microbiological status with the minimum risk for cross contamination between animals. Special attention has to be given to its maintenance and monitoring. Individually ventilated caging units are ergonomically suitable and they reduce the exposure of personnel to airborne allergens.